PENGARUH PROFITABILITAS LIKUIDITAS DAN LEVERAGE DALAM MEMPREDIKSI FINANCIAL DISTRESS - Wulandari, Sri; L.Tobing, Vargo Christian (SCIENTIA JOURNAL, 2019)
ABSTRACT The research object used are sub sector coal meaning companies which are listen in Indonesian Stock Exchange in 2013-2017. Purposive sampling techniue is used in this research for determining the resarch sample.The companies that has been choosen as the sample are 15 companie, the population are 22 companies. This research using quantitive approach. The variable in this research such as profitability, liquidity and leverage as independent variable financial distress as dependant variable. Data analysis used is descripitive analysis and multiple linear regression analysis. The result showed that profitability has significant influence towards the financial distress with significant level 0,017 < 0,05, liquidity does not have significant influence effect with significant level 0,259 > 0,05, leverage does not have significant influence effect with significant level 0,689 > 0,05. The result of regression analysis indicates that simultanieosly the profitability, liquidity and leverage does not have significant influence effect towards the financial distress with significant level 0,058 > 0,05. Adjusted R square value indicates that 6,1% of capital structure influenced by the the profitability, liquidity and leverage while the remaining 93,9% is influenced by other variables outside of this research.